Analysis Application Of Bioethical Principles In Horticultural Seeds Production At Horticultural Seed Development Medan: Analisis Penerapan Prinsip-Prinsip Bioetika Dalam Produksi Benih Hortikultura Di UPT. Pengembangan Benih Hortikultura Medan - Tiara Bunga Nainggolan; Theresia Cintya Ria Ambarita; Grecia Maranatha Nababan1; Ahmad Shafwan Pulungan; Nurbaity Situmorang (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2024)
The horticulture sector plays an important role in supporting food security. The availability of quality horticultural seeds is key to increasing the productivity of horticultural crops. Horticultural seed production involves various practices and techniques that can impact the environment, as well as issues such as genetic resource management, fairness in seed distribution, and community welfare. Bioethical principles must be considered to ensure horticultural seed production is done responsibly and sustainably. This research is a descriptive qualitative study that aims to describe and analyze the application of bioethical principles in horticultural seed production at the Horticultural Seed Development Unit Medan. Data were collected through literature studies, observations, and interviews with practitioners involved in horticultural seed production to gather information on the application of bioethical principles. The bioethical principles applied at the Horticultural Seed Development Unit Medan are kindness, harmlessness, and justice. The application of this principle is through conventional techniques of plant breeding, and the use of organic fertilizers. However, there are still weaknesses such as the use of chemical pesticides. Despite the challenges, efforts are made through guidelines, seed distribution programs, and collaboration with agricultural extension workers. The application of bioethical principles can support environmental sustainability and maintain food security. Recommendations include increasing awareness of the importance of bioethics, improving regulations, and developing bioethics training for researchers, technicians, and practitioners involved in horticultural seed production.